THE TRADITION OF SETTING THE TABLE WITH METAL AND FINE CERAMIC DISHES IN THE XVII–XІX CENTURIES - Rohotchenko, Oleksii; Kovalchuk, Ostap (Theory and practice of design, 2023)
Purpose. The purpose of the article is to highlight the peculiarities of the development of the tradition of table setting in European culture in the XVII–XІX centuries Methodology. The research methodology is based on art history methods and approaches focused on the analysis of metal and fine ceramic products that were used for serving. In addition, axiological, historical-chronological, historical-comparative and historical-cultural methods were applied, which allowed to reveal more deeply the main transformations of the types and characteristics of tableware during the XVII–XІX centuries. A cross-cultural analysis was used to compare tableware made of pewter, silver, and porcelain-faience. Results. It has been established that until the beginning of the XVIII century, metal objects, in particular tin and silver, prevailed in serving. The latter was characteristic mostly for the everyday use of monarchs and aristocracy of European states. It was found that at the beginning of the given century, porcelain dishes from China and earthenware from Delphi were widespread in everyday life. At the same time, it is determined that in the second half of the XVIII century, thin ceramic products of local production prevailed in serving, which gradually replaced silver ones. It was found that the number of tableware elements on the table was gradually expanding, the forms were changing and new ones were being actively added according to their purpose. Although the transformations, first of all, took place in France, Germany and England, tableware in Ukraine also underwent significant changes. Scientific novelty. The scientific novelty of the article is related to establishing the features of the transformations of the tradition of table setting in Europe, the characteristics of its products by purpose and materials. Practical relevance. The results of the study allow us to generalize and identify the key features of changes in the culture of table setting in European countries, including Ukraine in the XVII–XІX centuries.